Observation of the Intervention Effect of Biofeedback Therapy Combined With Cluster Nursing on Perioperative Constipation in Patients With Thoracolumbar Fracture - Luo, Jin; Xie, Nan; Yang, Liping (Frontiers in Surgery, 2022)
Purpose:To discuss the intervention effect of biofeedback therapy combined with cluster nursing on perioperative constipation in patients with thoracolumbar fracture. Methods:From June 2019 to June 2020, total of 482 patients with thoracolumbar fracture treated by surgery in our department were selected. Random number table method was used to divide into experimental group (n=241) and control group (n=241). The control group was given routine constipation care, The experimental group was given biofeedback therapy combined with cluster nursing based on the control group. The constipation score, Bristol stool scale score, SF-36 scale score, satisfaction of two groups were observed. Results:The constipation scores of the experimental group were lower than those of the control group, while the Bristol stool scale score, SF-36 score and satisfaction degree of the experimental group were higher than those of the control group (P<0.05). Conclusion:Biofeedback therapy combined with cluster nursing has a good intervention effect in perioperative constipation of patients with thoracolumbar fracture, which can reduce the degree of constipation, improve stool traits, improve the quality of life and improve the satisfaction of patients.